Who Am I Becoming? Identity Construction in Graduate Development Programs - Wöhnke,Clara; Wala,Miljaemilia Inka Maria (2025)
This study investigates how early-career professionals construct their professional identities within the context of graduate development programs. As organizations increasingly rely on graduate development programs to attract and develop high-potential graduates, these programs have become an important talent development strategy for cultivating future leaders. Yet, despite the growing prevalence of graduate development programs, there is limited research into how individuals themselves experience these programs and engage in identity construction within them. The study builds on qualitative semi-structured interviews conducted with ten individuals who completed a graduate development program in Sweden. Thematic analysis, guided by the Gioia methodology, was used to identify key themes in the data. The findings indicate that graduate development programs serve as spaces for identity work and identity play, where participants engage in exploring, forming, revising, protecting, strengthening and stabilizing their professional identities. Moreover, graduate development programs provide opportunities for leadership identity construction through social interactions, role experimentation, feedback, and mentorship, where participants engage in both adopting and revising leader identities. Further, the findings suggest that graduate development programs are treated as identity workspaces, offering holding environments that facilitate both identity work and identity play. This study extends the talent management and talent development literature by taking an identity perspective. Additionally, by offering empirical insights into identity construction from the individual's perspective, this study contributes to the literature on identity work, identity play, and identity workspaces. Moreover, the study offers practical implications for the design of graduate development programs, aimed at supporting early-career professionals to explore and consolidate their professional selves.
Keywords: talent development; graduate development programs; identity construction; identity work; identity play; leadership identity; identity workspaces